CD8+ T Cell Immunity Is Compromised by Anti-CD20 Treatment and Rescued by Interleukin-17A - Facundo Fiocca Vernengo (American Society for Microbiology, 2020)
ABSTRACT Treatment with anti-CD20, used in many diseases in which B cells play a pathogenic role, has been associated with susceptibility to intracellular infections. Here, we studied the effect of anti-CD20 injection on CD8+ T cell immunity using an experimental model of Trypanosoma cruzi infection, in which CD8+ T cells play a pivotal role. C57BL/6 mice were treated with anti-CD20 for B cell depletion prior to T. cruzi infection. Infected anti-CD20-treated mice exhibited a CD8+ T cell response with a conserved expansion phase followed by an early contraction, resulting in a strong reduction in total and parasite-specific CD8+ T cell numbers at 20 days postinfection. Anti-CD20 injection increased the frequency of apoptotic CD8+ T cells, decreased the number of effector and memory CD8+ T cells, and reduced the frequency of proliferating and cytokine-producing CD8+ T cells. Accordingly, infected anti-CD20-treated mice presented lower cytotoxicity of T. cruzi peptide-pulsed target cells in vivo. All of these alterations in CD8+ T cell immunity were associated with increased tissue parasitism. Anti-CD20 injection also dampened the CD8+ T cell response, when this had already been generated, indicating that B cells were involved in the maintenance rather than the induction of CD8+ T cell immunity. Anti-CD20 injection also resulted in a marked reduction in the frequency of interleukin-6 (IL-6)- and IL-17A-producing cells, and recombinant IL-17A (rIL-17A) injection partially restored the CD8+ T cell response in infected anti-CD20-treated mice. Thus, anti-CD20 reduced CD8+ T cell immunity, and IL-17A is a candidate for rescuing deficient responses either directly or indirectly. IMPORTANCE Monoclonal antibody targeting the CD20 antigen on B cells is used to treat the majority of non-Hodgkin lymphoma patients and some autoimmune disorders. This therapy generates adverse effects, notably opportunistic infections and activation of viruses from latency. Here, using the infection murine model with the intracellular parasite Trypanosoma cruzi, we report that anti-CD20 treatment affects not only B cell responses but also CD8+ T cell responses, representing the most important immune effectors involved in control of intracellular pathogens. Anti-CD20 treatment, directly or indirectly, affects cytotoxic T cell number and function, and this deficient response was rescued by the cytokine IL-17A. The identification of IL-17A as the cytokine capable of reversing the poor response of CD8+ T cells provides information about a potential therapeutic treatment aimed at enhancing defective immunity induced by B cell depletion.